1985
DOI: 10.1016/0039-6028(85)90840-4
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer distortion in the reconstructed (110) surface of Au

Abstract: A new LEED intensity analysis of the reconstructed Au(110)-(1×2) surface results in a modification of the missing row model with considerable distortions which are at least three layers deep. The top layer spacing is contracted by about 20%, the second layer exhibits a lateral pairing displacement of 0.07 .~ and the third layer is buckled by 0.24 ,~. Distortions in deeper layers seem to be probable but have not been considered in this analysis. The inter-atomic distances in the distorted surface region show bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
78
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(89 citation statements)
references
References 34 publications
11
78
0
Order By: Relevance
“…At low oxygen coverage, a single desorption peak at ~550 K is observed (Fig. S1), in agreement with previous studies [31] which also determined that saturation of this peak corresponds to one monolayer (ML) of oxygen (4 atoms per Au(110)-(1x2) unit cell [21]). …”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…At low oxygen coverage, a single desorption peak at ~550 K is observed (Fig. S1), in agreement with previous studies [31] which also determined that saturation of this peak corresponds to one monolayer (ML) of oxygen (4 atoms per Au(110)-(1x2) unit cell [21]). …”
Section: Methodssupporting
confidence: 91%
“…[19] Herein, we investigate the bonding of O on Au(110) in order to better exploit atomic-scale imaging using STM in conjunction with DFT studies. The Au(110) surface reconstructs to the missing-row Au(110)-(1x2) structure, which consists of an ordered array of (111) microfacets [20][21][22] capped by rows of atoms with low coordination number along the [1][2][3][4][5][6][7][8][9][10] direction (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…II A͒, our calculations still indicate a preference for reconstruction, which is in agreement with experiments. [4][5][6][7][8][9][10]32,34 In these experiments it was also observed that at elevated temperatures and an oxygen partial pressure of 5 ϫ 10 −11 atm there is coexistence of different reconstructed surfaces. This is also supported by our calculations, since the stability of the three reconstructed surfaces differs only by 1 -3 meV/ Å 2 , which is within the inaccuracy of the calculations.…”
Section: Resultsmentioning
confidence: 60%
“…While 3d and 4d metals, such as Cu͑110͒, Ag͑110͒, or Pd͑110͒, preferentially reconstruct after adsorption of alkali metals ͑e.g., Na, K or Cs͒, [1][2][3] 5d metals, such as Au͑110͒, Pt͑110͒, or Ir͑110͒, reconstruct already in their clean states. [4][5][6][7][8][9][10] In contrast to clean Au͑110͒ and Pt͑110͒ surfaces, which show a ͑1 ϫ 2͒-missing-row reconstruction, [11][12][13][14][15][16][17] the situation is more complex for Ir͑110͒ and a variety of potential surface structures have been reported. Here the strong tendency towards stable ͕111͖ microfacets and nanofacets seems to be the driving force for different surface reconstructions, trying to minimize the overall surface free energy.…”
Section: Introductionmentioning
confidence: 99%
“…This tendency is sketched in fig. 7 for the (1 x 2) "missing row" reconstructed (110) surfaces of Au [2], Ir [45], Pt [46,47] (fig. 7a), the hydrogen covered, (1 X 2) "paired row" reconstructed (110) surfaces of Ni [3] or Pd [43] (fig.…”
Section: Discussionmentioning
confidence: 99%